Effects of dextran sulfate, 4-t-butylcyclohexanol, pongamia oil and hesperidin methyl chalcone on inflammatory and vascular responses implicated in rosacea - Hernandez-Pigeon H; Garidou L; Galliano MF; Delga H; Aries MF; Duplan H; Bessou-Touya S; Castex-Rizzi N (Clinical, Cosmetic and Investigational Dermatology, 2018)
Hélène Hernandez-Pigeon, Lucile Garidou, Marie‑Florence Galliano, Hélène Delga, Marie‑Françoise Aries, Hélène Duplan, Sandrine Bessou-Touya, Nathalie Castex-Rizzi Department of Pharmacology, Pierre FABRE Dermo-Cosmétique R&D Center, Toulouse, France Background: Rosacea is a chronic facial skin disorder characterized by inflammation and vascular abnormalities. The pathophysiology of rosacea involves increased activation of the capsaicin receptor, TRPV1, the vascular endothelial growth factor (VEGF) pathway, and cathelicidin LL-37, MMP-9, and KLKs. We evaluated the activity of four compounds (dextran sulfate, 4-t-butylcyclohexanol [BCH; TRP-regulin®], pongamia oil, and hesperidin methyl chalcone [HMC]) on inflammatory and vascular responses implicated in rosacea.Materials and methods: The anti-inflammatory activity of dextran sulfate was evaluated on PGE2 production after PMA stimulation of NCTC-2544 keratinocytes, and on normal human epidermal keratinocytes (NHEKs) after proinflammatory stimulation to mimic a rosacea environment. The anti-angiogenic activity of dextran sulfate was measured by analyzing pseudotube formation in co-cultured human microvascular endothelial cells/normal human dermal fibroblasts. HMC modulation of vascular responses and IL-8 cytokine production after SP stimulation was evaluated in human skin explants. We also assessed the effect of BCH on TRPV1 activation, and the effect of combined BCH and pongamia oil on the inflammatory response of NHEKs.Results: Dextran sulfate strongly and significantly inhibited PMA-induced PGE2 production, inhibited KLK5 and MMP-9 mRNA expression, and IL-8, IL-1α and VEGF production, and displayed a highly significant inhibitory effect on VEGF-induced pseudotube formation. In SP-stimulated human skin explants, HMC significantly decreased the proportion of dilated vessels, total vessel area, and IL-8 production. BCH significantly and dose-dependently inhibited TRPV1 activation, and BCH and pongamia oil inhibited CXCL1 and CXCL6 mRNA expression and IL-8 production in NHEKs. Combined BCH/pongamia oil inhibited IL-8 production synergistically.Conclusion: These in vitro results showed that dextran sulfate, BCH, pongamia oil and HMC, possess complementary soothing and anti-redness properties, supporting their combination in Avène redness-relief cosmetic products for sensitive skin prone to redness, and for topical adjunctive rosacea treatment. Keywords: rosacea, keratinocyte, inflammation, redness, VEGF